Financial Provision by Migrant Husbands and Its Impact on Family Resilience in Kampar Regency, Riau - Hardani, Sofia; Abdul Munir, Akmal; Mochammad Sahid, Mualimin; Nelli, Jumni; Hasanah, Nur (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This article examines the complexities of family life among women whose husbands migrate for work in Kampar Regency, Riau, with a focus on how financial obligations are fulfilled and how these conditions affect family resilience in economic, social, and psychological dimensions. The study employs a qualitative approach using in-depth interviews with ten informants, consisting of wives, children, and community leaders. The findings reveal that the tradition of migration has long been embedded in Kampar’s cultural practices, leading to a generally positive acceptance of the migrant-husband phenomenon. Financial support in the form of remittances emerges as the primary factor sustaining family resilience, complemented by emotional support delivered mainly through communication. Social support, religiosity, and the contributions of children also play significant roles in strengthening family resilience. Conversely, challenges such as delayed remittances, infrequent communication, and moral issues including second marriages undertaken while living away pose serious threats to family stability. This article contributes academically to the development of family integrity theory and offers practical insights for policymakers and communities in formulating strategies for family empowerment.